Lifestyle Modification through Dietary Intervention: Health Promotion of Patients with Non-Alcoholic Fatty Liver Disease - Manoochehr Khoshbaten; Alireza Farsad Naeimi; Mehrangiz Ebrahimi-Mameghani; Seyed Rafie Arefhosseini; Javad Rashid (Tabriz University of Medical Sciences, 2011)
Background: Prevalence of non-alcoholic fatty liver disease (NAFLD) is more common worldwide and no certain treatment apart from lifestyle modification has been established yet. Available data consistently show that energy intake is significantly higher in patients with NAFLD than in individuals with no evidence of fatty liver. Changing nutritional behaviors seems to be the primary approach for treatment, simultaneously addressing all the clinical and biochemical defects. This study was aimed to examine the effects of two different composition of low energy diet (diet I vs. diet II) on non-alcoholic fatty liver disease patients.Methods: In this double-blind randomized controlled trial, 44 ultrasonography-proven overweight non-alcoholic fatty liver disease patients were divided into two groups and received two low-energy diets (-500 kcal less than energy requirement individually) inc. diet I (Carbohydrate: Fat: Protein: 55:25:20) and diet II (Carbohydrate: Fat: Protein: 40:40:20) for six weeks. Anthropometric and biochemical measures as well as liver enzymes were assessed after 12 hours fasting.Results: After diet I and diet II, weight decreased significantly (%1.82 and %2.45, respectively). Liver enzymes and echogenicity decreased significantly by both diet I and diet II. Mean of triglyceride concentration decreased (%18.09) after diet II (P=0.023), while there was no significant change after diet I. Significant correlations were found between changes in aspartate aminotransferase with triglyceride and LDL-C diet I.Conclusion: Low energy diets can decrease liver enzymes regardless of their composition, while diet II seems to be more effective than diet I in reduction of weight and triglyceride level.